Dose-related patterns of glucocorticoid-induced side effects. Issue 7 (6th August 2008) - Huscher, D; Thiele, K; Gromnica-Ihle, E; Hein, G; Demary, W; Dreher, R; Zink, A; Buttgereit, F
Abstract : Objective: To identify patterns of self-reported health problems relating to dose and duration of glucocorticoid intake in unselected patients with rheumatoid arthritis from routine practice. Methods: Data from 1066 patients were analysed. The clinical status and drug treatment were reported by the physician, health problems during the past 6 months by the patient using a comprehensive list of symptoms. Patients with ongoing glucocorticoid treatment for more than 6 months and current doses of less than 5, 5–7.5 and over 7.5 mg/day prednisone equivalent were compared with a group without any glucocorticoid treatment for at least 12 months. Results: The frequency of self-reported health problems was lowest in the group without glucocorticoid exposition and increased with dosage. Two distinct dose-related patterns of adverse events were observed. A "linear" rising with increasing dose was found for cushingoid phenotype, ecchymosis, leg oedema, mycosis, parchment-like skin, shortness of breath and sleep disturbance. A "threshold pattern" describing an elevated frequency of events beyond a certain threshold value was observed at dosages of over 7.5 mg/day for glaucoma, depression/listlessness and increase in blood pressure. Dosages of 5 mg/day or more were associated with epistaxis and weight gain. A very low threshold was seen for eye cataract (<5 mg/day). Conclusion: The associations found are in agreement with biological mechanisms and clinical observations. As there is a paucity of real-life data on adverse effects of glucocorticoids prescribed to unselected groups of patients, these data may help the clinician to adapt therapy with glucocorticoids accordingly and improve the benefit–risk ratio.